IS IT TRUE THAT PPAk A MEANS OF ACCOUNTING MARKET SLAVERY? - Jurana,Muhammad Darma Halwi,Nina Yusnita Yamin, Muhammad Ansar (International Journal of Advanced Science and Technology, 2020)
The purpose of this study was to find other meanings of the implementation of PPAk in Indonesia and at the same time find a solution to the problems contained in the Program of Professional Accounting Education (PPAk). The approach used in this study was a critical approach. This study used momong method. Momong was used as a way for researchers to nurture and open awareness to informants on the current concerns about the provision of PPA education. Data collection in this study was performed by in-depth interviews with informants after going through the nurturing process (momongi). In-depth interviews were conducted to lecturers who teach at PPAk, and related officials and had in-depth knowledge related to PPAk implementation. This study also used the reflexivity of researchers in finding solutions that should be performed in improving the education system in PPAk. This study found that PPAk is a means of accounting market slavery. In addition, the results of the study also found inconsistencies or asynchronous rules made by several ministries related to the implementation of PPA so that there was a setback for the existence of PPAk. Therefore, to overcome this situation, the PPAk should be used as a means of transferring moral, religious, and nationalism values. This was performed by basing morals, religious, and nationalism values in the existence of PPAk.